Engineering of a trispecific tumor-targeted immunotherapy incorporating 4-1BB co-stimulation and PD-L1 blockade. (1st January 2021) - Warmuth, Stefan; Gunde, Tea; Snell, Daniel; Brock, Matthias; Weinert, Christopher; Simonin, Alexandre; Hess, Christian; Tietz, Julia; Johansson, Maria; Spiga, Fabio Mario; Heiz, Robin; Flückiger, Naomi; et al.
ABSTRACT: Co-stimulatory 4–1BB receptors on tumor-infiltrating T cells are a compelling target for overcoming resistance to immune checkpoint inhibitors, but initial clinical studies of 4–1BB agonist mAbs were accompanied by liver toxicity. We sought to engineer a tri-specific antibody-based molecule that stimulates intratumoral 4–1BB and blocks PD-L1/PD-1 signaling without systemic toxicity and with clinically favorable pharmacokinetics. Recombinant fusion proteins were constructed using scMATCH3 technology and humanized antibody single-chain variable fragments against PD-L1, 4–1BB, and human serum albumin. Paratope affinities were optimized using single amino acid substitutions, leading to design of the drug candidate NM21-1480. Multiple in vitro experiments evaluated pharmacodynamic properties of NM21-1480, and syngeneic mouse tumor models assessed antitumor efficacy and safety of murine analogues. A GLP multiple-dose toxicology study evaluated its safety in non-human primates. NM21-1480 inhibited PD-L1/PD-1 signaling with a potency similar to avelumab, and it potently stimulated 4–1BB signaling only in the presence of PD-L1, while exhibiting an EC50 that was largely independent of PD-L1 density. NM21-1480 exhibited high efficacy for co-activation of pre-stimulated T cells and dendritic cells. In xenograft models in syngeneic mice, NM21-1480 induced tumor regression and tumor infiltration of T cells without causing systemic T-cell activation. A GLP toxicology study revealed no evidence of liver toxicity at doses up to 140 mg/kg, and pharmacokinetic studies in non-human primates suggested a plasma half-life in humans of up to 2 weeks. NM21-1480 has the potential to overcome checkpoint resistance by co-activating tumor-infiltrating lymphocytes without liver toxicity.